Pengembangan Bahan Ajar E-Modul Berbasis Discovery Learning Berbantu Simulasi PhET (Physics Education Technology) pada Materi Energi untuk Meningkatkan Hasil Belajar Peserta Didik - Alfi Andriani (LPPM IAI Nasional Laa Roiba Bogor, 2023)
This study aims to produce a product in the form of discovery learning-based e-modules assisted by PhET simulation on energy material that is feasible to use, analyze the level of validity, practicality, and effectiveness to improve student learning outcomes. This research uses research and development (R&D) method with ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The samples in this study were 9 students of class VIII-2 for small scale and 27 students of class VIII-2 for large scale. The research instruments used in this study were material expert and media expert validation questionnaires, practicality questionnaires by educators and students, and to determine the effectiveness of e-modules by giving pretest and postest questions to students. At the validation stage, the results of the material expert assessment received an average percentage of 94% with a very feasible category. The results of the media expert assessment received an average percentage of 82% with a very feasible category. The results of the educator response assessment for the practicality test get an average percentage of 84% with a very practical category. The results of the practicality test by students from the questionnaire given both small-scale and large-scale tests get an average percentage of 94% and 93% with a very practical category. The results of the effectiveness test on learning outcomes obtained an n-gain of 0.58 with a fairly effective category in the experimental class and 0.46 with a less effective category in the control class. The result of the tcount value (1.98) > ttable (1.67), so H0 is rejected and Ha is accepted. This shows that the e-module developed is very feasible, practical and effective to use as teaching material in learning activities.